An organizational model for intentions to adopt blockchain-based hospital information systems in Malaysian hospitals - Bazel, Mahmood Abdullah Moqbel (2024)
Blockchain technology has gained considerable interest in various sectors due to its distributed ledger, decentralized nature, and cryptographic security. Despite its potential to revolutionize the healthcare industry by providing a unified and secure system for health records, blockchain adoption remains limited in developing countries including Malaysia. The current literature lacks comprehensive empirical studies investigating the factors influencing the adoption of blockchain technology in the healthcare sector. Thus, this study aims to identify the factors influencing the intention to adopt blockchain technology in Malaysian healthcare domain. A theoretical model is proposed by integrating the Fit-Viability Model (FVM), Technological-Organizational-Environmental (TOE) framework, and institutional theory (INS) to examine these factors. A quantitative approach was adopted, and data was collected through an online survey of 199 decision-makers in Malaysian hospitals. The collected data were analysed using Partial Least Squares (PLS) analysis. The results indicate that trust, information transparency, disintermediation, cost-effectiveness, top management support, organizational readiness, partner readiness, technology vendor support, fit, and viability significantly and positively influence the intention to adopt blockchain-based Health Information Systems (HIS) in Malaysian hospitals. Conversely, coercive pressure from the government negatively affects the adoption decision. Moreover, the study found that hospital ownership type does not moderate the relationships between the identified factors and blockchain technology adoption. This study provides valuable insights into the various factors that influence blockchain technology adoption in public and private hospitals. The developed model offers guidelines for hospitals, blockchain technology providers, governments, and policymakers to devise strategies that promote implementation and encourage the widespread adoption of blockchain technology in Malaysian healthcare organizations.